PENGARUH STATUS GIZI TERHADAP POTENSI INTELEKTUAL ANAK USIA SEKOLAH : DI SDIT BINA INSANI LIRBOYO KEDIRI - Susilowati, Erna; rahmawati, Elfi Quyumi (Universitas Nusantara PGRI Kediri, 2020)
ABSTRACT Low nutritional status has an impact on a child's cognitive abilities so that the child's development has been delayed. Negligence and lack of attention in handling and fulfilling the nutritional needs of school-age children has a sustained impact on growth and development in the next period of their lives. The purpose of this study was to determine the effect of nutritional status on the intellectual potential of school-age children. This study was an observational study with a cross sectional design, a large sample of 32 children with a simple random sampling method, with data analysis using a kendall's tau. Nutrition status data is obtained by measuring body weight and age and body mass index. presented with height Z-score according to age (TB / U) IQ data obtained from tests of intellectual potential. The results use spearman rho showed value 0,016 which shows influence between nutritional status on the intellectual potential of school-age children. There is an influence of nutritional status on the ability of understanding, verbal ability, numerical ability, logical thinking ability and abstract thinking. With early detection of nutritional status and improvement of children's nutritional status can be done so that it is expected that delays in child development can be prevented and IQ increased Keyword:, nutritional status, intellectual abilities